How mortality risk estimated by MAGGIC-HF, SHFM and BCN-Bio HF scores is modified after 12-month management in a multidisciplinary HF Clinic. (25th November 2020) - Codina, P; De Antonio, M; Santiago-Vacas, E; Domingo, M; Zamora, E; Santesmases, J; Subirana, I; Buchaca, D; Alonso, N; Troya, M.I; Velayos, P; Pulido, A; et al.
Abstract: Background: Heart failure (HF) contemporary management has significantly improved over the past two decades leading to better survival. How application of the contemporary HF management guidelines affects the risk of death estimated by available web-based risk scores is not elucidated. Objective: To assess changes in mortality risk prediction after a after a 12-month management period in a multidisciplinary HF Clinic. Methods: Out of 1, 689 consecutive patients with HF admitted at our ambulatory HF Clinic from May 2006 to November 2018, those who completed one year follow-up were considered for the study. Patients without NTproBNP measurement or with more than 3 missing variables for risk estimation were excluded. Three contemporary web-based HF risk scores were evaluated: MAGGIC-HF, Seattle HF Model (SHFM) and the Barcelona Bio-HF Calculator containing NTproBNP (BCN Bio-HF). Risk of all-cause death at one year and at 3 years were calculated at baseline and re-evaluated after 12-month management in a multidsisciplinary HF Clinic. Wilcoxon paired data test was used to compare changes in mortality risk estimation over time and test equality of matched pairs for comparing estimated change among tools. 442 patients used to derive the Barcelona Bio-HF Calculator were excluded for discrimination purposes. Results: 1, 157 patients were included (age 65.7±12.7 years, 70.4% men). A significant reduction in mortality risk estimation was observed with the three HF risk scores evaluated at 12-months (Table). The BCN Bio-HF model showed significantly different changes in risk estimation, fact that indeed was partnered with numerically better discrimination. AUC at 1 and 3 years, respectively, were: BCN Bio-HF (0.773 and 0.775), MAGGIC HF (0.686 and 0.748) and SHFM (0.773 and 0.739). Conclusions: The three web-based risk scores evaluated showed a significant reduction in mortality risk estimation after 12 month management in a multidisciplinary HF Clinic. The BCN Bio-HF score showed higher reduction in estimated risk, together with better discrimination, likely because it incorporates contemporary treatment and use of biomarkers. Funding Acknowledgement: Type of funding source: None